1.6 V high-voltage aqueous symmetric micro-pseudocapacitors based on two-dimensional polypyrrole/graphene nanosheets. (July 2022) - Chi, Liping; Zheng, Shuanghao; Ma, Jiaxin; Liu, Yu; Xing, Fei-Fei; Zhou, Feng; Wang, Shaoxu; Wu, Zhong-Shuai
Abstract: Pseudocapacitive micro-supercapacitors (MSCs) have been regarded as miniaturized electrochemical energy storage devices with prominent features for seamless integrating wearable electronic devices. However, the electrochemical performance remains challenging due to the low voltage of aqueous electrolyte. Herein, we constructed aqueous pseudocapacitive MSCs (PPy@rGO-MSCs) with a high operation voltage of 1.6 V using hybrid polypyrrole (PPy) and reduced graphene oxide (PPy@rGO) nanosheets working in 20 M LiCl gel electrolyte. The pseudocapacitive MSCs with interdigital planar geometry were manufactured by one-step mask-assisted filtration on a flexible substrate. The as-fabricated PPy@rGO-MSCs in 20 M LiCl electrolyte showed higher areal capacitance of 44.5 mF/cm 2 and improved areal energy density of 15.8 μWh/cm 2, in comparison with the cell in 20 M LiTFSI electrolyte (35.7 mF/cm 2, 12.7 μWh/cm 2 ). Additionally, PPy@rGO-MSCs exhibited excellent mechanical flexibility with 97% of initial capacitance retention at a bending angle of 180°, and superior integrated modular to boost voltage and current output. This work demonstrates that 2D pseudocapacitive materials hold a great chance for constructing high-performance MSCs. Graphical abstract: The aqueous pseudocapacitive MSCs with a high operation voltage of 1.6 V are demonstrated based on 2D polypyrrole/graphene hybrid nanosheets working in 20 M LiCl gel electrolyte, showing high energy density, excellent flexibility and superior integration. Image 1